INTRA-SENTENTIAL CODE-SWITCHING IN YEAR 5 ENGLISH CLASSROOM: A STUDY ACROSS FIVE SELECTED NATIONAL PRIMARY SCHOOLS - Mohan , Vijaya; Ramakrishna , Rita Abdul Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study explores the types of intra-sentential code-switching (CS) used by Year 5 pupils during English lessons in five selected national primary schools on Penang Island, Malaysia. The purpose of the study is to examine how bilingual pupils employ different types of CS to navigate linguistic challenges and enhance classroom communication. The study is based on Muysken’s (2000) typology of intra-sentential CS, which includes alternation, insertion, and congruent lexicalization. A qualitative research design was used. Data were collected through classroom observations involving audio recordings of 160 English lessons. All the recordings were transcribed verbatim and analysed thematically using Braun and Clarke’s (2006) six-phase framework. The findings reveal that insertion was the most frequently used form of CS. Pupils used it to fill lexical gaps and maintain fluency. Alternation occurred at clause boundaries to facilitate clarification. Congruent lexicalization was observed when pupils blended elements from different languages using compatible grammatical structures. Pupils used CS to support vocabulary, clarify meaning, and assist peers during lessons. The study concludes that intra-sentential CS serves several communicative purposes among bilingual pupils. These findings provide valuable insights for English language teachers working in multilingual classrooms. Understanding the types and functions of CS may help teachers design instructional strategies that accommodate pupils’ bilingual capabilities while supporting their English language development. The study also contributes to the growing body of knowledge on bilingual speech in Malaysian primary schools and reinforces the significance of code-switching as a pedagogical resource rather than an obstacle in language learning.